Comparative Genetic Analysis of Durum Wheat Landraces and Cultivars Widespread in Tunisia - Miazzi, Monica Marilena; Babay, Elyes; De Vita, Pasquale; Montemurro, Cinzia; Chaabane, Ramzi; Taranto, Francesca; Mangini, Giacomo (Frontiers in Plant Science, 2022)
The durum wheat landraces constitute a useful natural germplasm for to increase the genetic diversity in modern durum cultivar. The Tunisian durum germplasm is constituted by few accessions conserved in Gene Bank of Tunisia which are still unexplored. In this work, a comparative genetic analysis was performed to investigate the relationships between the Tunisian durum lines and the modern cultivars and to detect divergent loci involved in breeding history. The genetic diversity analyses. carried out using 9 morphological descriptors and the 25K SNP array, allowed to distinguish two groups of Tunisian landraces, and one of the durum cultivars. The AMOVA and diversity index confirmed the genetic variability among the groups. A total of 529 SNP loci resulted divergent between Tunisian durum landraces and modern cultivars. Candidate genes were identified related to plant and spike architecture including FLOWERING LOCUS T (FT-B1), Zinc finger CONSTANS and AP2/EREBPs transcription factors. In addition, divergent genes involved in grain composition and biotic stress (NBS-LRR and RPM) were found, suggesting that the Tunisian durum germplasm may represent an important source of favorable alleles to be used in future durum breeding programs for developing well-adapted and resilient cultivars.